RU sleepy? - sleep/wake characteristics and sleep quality among undergraduate students attending Rhodes University - Young, Celine Brittany (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics)
Background: University students, specifically older adolescents and young adults, are at high risk of insufficient and poor-quality sleep due to age-related biological changes converging with several systemic factors unique to the university context. These include but are not limited to freedom and independence, communal living environments, academic demands and associated stress, erratic schedules, and high technology use. While there has been extensive research on sleep quality in students in other parts of the world, there has been comparatively less in South Africa, which may present unique contextual influencing factors. Thus, this study aimed to characterise sleep/wake characteristics and sleep quality in a sample of undergraduate students attending a South African University. Additionally, the study aimed to determine the impact of certain demographic factors on sleep quality in the students. Lastly, the current study aimed to determine what factors may influence the students' sleep quality. Method: This study adopted a cross-sectional design and explored sleep quality and sleep/wake characteristics (e.g., bedtimes, rise times, sleep duration, sleep latency, etc.) through an online survey circulated amongst undergraduate students via Rhodes university email platforms and student social media pages. The testing period started on 15 August 2022 and continued until 8 October 2022. The survey consisted of three main sections: (1) socio-demographic factors; (2) the Pittsburgh Sleep Quality Index (PSQI); (3) an open-ended question that asked students to comment on the factors which they felt may be influencing their sleep over the previous month. Results: 393 students participated in this study, which corresponds to a response rate of 6.30%. The results revealed notable levels of poor sleep quality (mean global score of 9.79 (Â±3.36)) and a high prevalence of poor sleepers within the whole sample (over 90%), as well as across different demographic groups. Analysis indicated poor overall sleep quality, and concerning sleep/wake characteristics, such as, bedtimes, rise times, sleep latency, time in bed, habitual sleep efficiency, sleep duration, etc. Additionally, participants reported extended sleep latencies and difficulties initiating sleep within 30 minutes. Daytime dysfunction was prominent, indicating challenges in daily functioning. Demographic comparisons revealed that male students generally reported better subjective sleep quality and lower global PSQI scores than female students, with 2 females presenting with poorer sleep quality overall. Students living in university residences reported significantly later bedtimes and shorter sleep durations than off- campus students. Regarding year of study, third-year students reported better subjective sleep quality, longer times in bed, longer sleep durations and overall better sleep quality than first- and second-year students. Regarding funding mechanisms, students on the National Students Financial Aid Scheme had significantly higher subjective sleep quality scores but later bedtimes than students in the "other" funding groups. Thematic analysis revealed that several self-reported factors impacted student sleep negatively. Mental health issues were the most commonly cited theme (26.72% of students), which included anxiety, stress, worry, and overthinking. University-related factors were the second most frequently cited theme (25.49% encompassing academics, funding, and navigating university life). Environmental influences comprised of issues with noise, particularly in university residences, weather, and lighting. Discussion: In sum, the results of this study indicate that in this sample, the drivers of poor sleep quality seemed to be late bedtimes, early rise times, prolonged sleep latency, frequent night awakenings, and overall short sleep duration, all of which were driven by several systemic factors. These findings underscore the importance of assessing sleep health beyond just sleep duration and indicate compromised sleep health within this population, evidenced by high levels of daytime dysfunction due to inadequate and poor-quality sleep. The challenges faced by university students extend across various aspects of their lives, including sleep health, with poor sleep quality and insufficient sleep having significant implications for academic performance, mental health, and overall well-being as they transition into adulthood.
Keywords: Undergraduates -- South Africa -- Makhanda; Sleep quality; Sleep-wake cycle; Pittsburgh Sleep Quality Index; College students -- Social conditions